THE COMPARISON OF CALCIUM OXALATE CONCENTRATIONS WITH DIFFERENT EXTRACTION METHODS IN PORANG FLOUR (AMOPHALUS MUELLERI BLUME) - Suci Hardina Rahmawati; Novita Herdiana (Politeknik Negeri Lampung, 2023)
This study aims to compare the concentration of calcium oxalate in porang flour (Amophalus Muelleri Blume) using different extraction methods. The extraction method used is direct (non-stratified) extraction and stratified extraction. The percentage of purity of porang flour from multistage and non-stratified extraction, respectively, was 2.16% and 2.62%. Efficiency of ethanol content in the direct/non-staged purification process is 80% ethanol, while for the graded efficiency the levels are 40%, 60%, and 80%. Visual observations including flour color, viscosity, and proximate test showed purification of porang flour using graded extraction gave better results than ordinary/unstaged extraction.